2004
DOI: 10.1021/jo0358168
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Bromomethylazoles and Tosylmethyl Isocyanide. A Novel Heterocyclization Method for the Synthesis of the Core of Marine Alkaloids Variolins and Related Azolopyrimidines

Abstract: A novel and efficient synthesis of the pyrido[3',2':4,5]pyrrolo[1,2-c]pyrimidine system, the heterocyclic core of the variolin family of marine alkaloids, is described. The route involves the reaction of 3-bromo-2-(bromomethyl)pyrrolo[2,3-b]pyridine and tosylmethyl isocyanide (TosMIC) under phase-transfer conditions. This unprecedented reaction was also used to synthesize a series of new methoxycarbonyl azolopyrimidines by reaction of TosMIC with bromomethylindoles, bromomethylbenzimidazole, and bromomethylpyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…This derivative cleanly reacted with TosMIC under phase-transfer (PTC) conditions (TBAI/NaOH/CH 2 Cl 2 ) to afford the unexpected methyl 5-bromopyrido[3Ј,2Ј:4,5]pyrrolo[1,2-c]pyrimidine-7-carboxylate (7a) in 65 % yield. The mechanism proposed [10] to account for the formation of 7a involves initial nucleophilic substitution of TosMIC on the bromomethylpyrrole followed by intramolecular transfer of the methoxycarbonyl protecting group. Subsequent attack of the pyrrole nitrogen on the isocyanide group would lead to cyclization and 1,2-elimination of p-toluenesulfinic acid to afford 7a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This derivative cleanly reacted with TosMIC under phase-transfer (PTC) conditions (TBAI/NaOH/CH 2 Cl 2 ) to afford the unexpected methyl 5-bromopyrido[3Ј,2Ј:4,5]pyrrolo[1,2-c]pyrimidine-7-carboxylate (7a) in 65 % yield. The mechanism proposed [10] to account for the formation of 7a involves initial nucleophilic substitution of TosMIC on the bromomethylpyrrole followed by intramolecular transfer of the methoxycarbonyl protecting group. Subsequent attack of the pyrrole nitrogen on the isocyanide group would lead to cyclization and 1,2-elimination of p-toluenesulfinic acid to afford 7a.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Herein we describe in detail our synthetic studies towards the synthesis of variolins, which have led to a conceptually different convergent approach to variolin B and deoxyvariolin B. [11] Our approach is well suited not only for the synthesis of the natural alkaloid but also for the eventual structural modification of the natural product by using sequential palladium-mediated C-N, C-C, and C-O coupling reactions for the installation of key structural substituents on a trihalo-substituted pyrido[3Ј,2Ј:4,5]pyrrolo [1,2-c]pyrimidine, which is a key intermediate.…”
Section: Pyridine)mentioning
confidence: 99%
“…This organotin compound was obtained by palladium-catalyzed halogen-tin exchange employing hexamethylditin and cross-coupled with the brominated tricyclic compound 208 to give the corresponding derivative 209, which is related to variolin marine alkaloids. 384 Similar 4-stannylpyrimidines have been used in the total synthesis of variolin B 385 and deoxyvariolin B. 385b Moreover, 5-stannylated pyrimidines have been used in palladium-catalyzed couplings to give iodoimidazole-containing nucleosides for new base pairing motifs, 386 and also in the preparation of structures for supramolecular assemblies, after double coupling to 5,10-dibromoanthracenes.…”
Section: Scheme 61mentioning
confidence: 99%
“…These compounds have been described as being DNA cleaving agents [1], DNA gyrase inhibitors [2][3][4][5][6][7], antiinflammatory [8][9][10], antiamoebic and analgesic [8,9], herbicidal [11], antimicrobial and antifungal [12], antiulcer [13], polymer dye additive [14], variolin alkaloids analogues [15][16][17], and nucleoside analogues agents [18,19]. Studies on benzene carcinogenesis and mutagenesis showed that p-benzoquinone which is the oxidation product of benzene reacts with deoxycitidine in the human body [20][21][22][23][24][25][26][27] to produce a pyrimido [1,6-a]benzimidazole structure as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%